Using of the Politeness Principle in Dissertation Writing: Focus on the English Department of the Teacher Training College of Mbujimayi (International Journal of Scientific Research and Management (IJSRM), 2023)
Communication is oral, written, etc. When we communicate through writing or any other way, we should pay attention to our addressee or interlocutor so as to avoid hurting the latter, be it in speaking or writing. I was shocked to notice students are not prudent to the way they are addressing to others: teachers, pupils, inspectors and so on. The speaker or writer of any language should respect some established principles of that language i.e. the communication in any language is interesting when it implies the use and respect of that languages’ politeness rules. I have selected twenty dissertations from the department of English of the Teacher Training College of Mbujimayi, DRC. These dissertations are from different domains: grammar, theoretical linguistics, and literature or applied linguistics. I have been focused on dissertations sections such as: Problem definition, choice and interest of the work, aims and purposes of the study, and further studies. I have noticed that the politeness maxims are more violated in dissertations than they are observed. To avoid violating more the politeness principle (PP) in both speaking and writing, I have suggested that the PP get taught to students in conversations and research methodology courses. Students should be familiarized to practicing the PP maxims in classroom reports and debates, in essay writing, in letters, etc.